Trashing Scale: Distributed Agency, the Afterlife of Commodities and Animism in Contemporary Art. Issue 3 (4th May 2021) - López Cuenca, Alberto
Abstract: This article provides a conceptual and historical approach to frame the recurrent use of animism in contemporary art and theory. It calls attention to the 'anthropological turn' that took place in the 1980–1990s that characterised objects and artworks as agents, and revise the notion of the 'socialist object' to define the kind of agency commodities have achieved in late capitalism. It argues that the current interest in new forms of agency can be related to an animistic object resulting from the overlapping of flexible commodities and diffuse things: garbage. Pollution and waste are generating unpredictable kinds of agency that are engulfing humans in unprecedented assemblages. The article specifically focuses on how two artistic projects – Adriana Salazar's The Animistic Museum of Texcoco Lake (2018) and TRES art collective's Ubiquitous Trash (2016) – engage with different notions of animism and trash in their devising of experimental post-humanist scales.